Evaluasi Implementasi Kebijakan Pemerintah Kota Yogyakarta Mengenai Pendidikan Inklusi - Astri Hanjarwati; Siti Aminah (PLD UIN Sunan Kalijaga, 2014)
The main problem encountered in the field of education in Yogyakarta is the large number of children with special needs who do not get adequate educational services. Schools in the city of Yogyakarta tend to rejectandon the other hand, are lessaccessible to the crew. The number of complaints from the public push for education reformin the city of Yogyakarta, namely inclusive education. In 2008, drafted onthe concept of inclusive education policy in the city of Yogyakarta, which is then passed into the Mayor Regulation No.47 in 2008. With the inclusi on of education policy, the crew can obtain equivalent education with other normal children. A subsequent stage after the Mayoris Regulations Technical Guidance (technical guidelines) the implementation ofinclusive education. After completion oftechnical guidelines drawn up, the socialization and awareness of teachers in schools ranging from kindergarten tohigh school/vocational school in the city of Yogyakarta.